Development of a new analytical method for the determination of red beetroot betalains using dispersive solid‐phase extraction. Issue 15 (8th July 2016) - Sawicki, Tomasz; Surma, Magdalena; Zieliński, Henryk; Wiczkowski, Wiesław
Abstract : The objective of this study was to develop a method for the determination of red beetroot betalains based on the dispersive solid‐phase extraction and modified QuEChERS methods followed by micro‐high performance liquid chromatography coupled with a mass spectrometer that was equipped with a quadrupole and time‐of‐flight detector. Currently, new techniques for the extraction of the pigments are necessary and in this study, an extraction of beetroot betalains based on the QuEChERS method was developed for the first time. Twelve variants of the methods with different sorbent combinations were tested. The extraction with 15% methanol and with 0.05% formic acid was performed as a reference method to compare the obtained results. In all of the samples with the addition of sorbents, a lower noise was demonstrated in the obtained results. The betalain concentrations obtained using the tested methods were 0.32–0.54 mg g −1, while the value of the reference method was 0.44 mg g −1 . The method that used the strong ion exchange sorbent (0.44±0.05 mg g −1 ) was the most adequate in terms of analyzed content, related standard deviation value and interference compared to the reference method. It was concluded that the properly modified QuEChERS method can be successfully applied for the determination of red beetroot betalains.